Influence of Different Annealing Temperatures on the Structural and Optical Properties of TiO2 Nanoparticles Synthesized via Sol-Gel Method: Potential Application as UV Sensor - Nur Munirah Safiay; Rozina Abdul Rani; Najwa Ezira Ahmed Azhar; Zuraida Khusaimi; Fazlena Hamzah; Mohamad Rusop (Universitas Gadjah Mada, 2021)
In this research, TiO2 thin films were prepared using a simple sol-gel spin coating process. The films were characterized using Field Emission Scanning Electron Microscopy (FE-SEM), Energy Dispersive Ray (EDX), X-ray diffraction (XRD) and Ultraviolet–visible Spectrophotometer in order to investigate the influence of different annealing temperatures to the structural and optical properties of TiO2. The surface morphology images from FE-SEM display a uniform layer of nanoparticles with a sample of 500 °C possess the most uniform and the visible spherical grain of TiO2 nanoparticles. EDX spectra confirm the presence of Ti and O elements in the samples. The structural properties from the XRD pattern demonstrate that the films are crystalline at a temperature of 500 and 600 °C and the peak (101) intensity was increased as the annealing temperature increased. They exist in the anatase phase at the preferred plane orientation of (101). The calculated crystallite size for 500 and 600 °C samples is 19.22 and 28.37 nm, respectively. The films also possessed excellent absorption in the ultraviolet (UV) region with optical band gap energy ranging from 3.32 to 3.43 eV. These results can be fundamental for the fabrication of a UV sensing device.